Pelatihan Hidroponik Sistem Sederhana pada Skala Rumah Tangga di Desa Salo, Kecamatan Salo, Kabupaten Kampar, Riau - Razita Hariani; Anna Dhora; Ardiansyah Hamid; Fajar Aga Wandana; Niken Ellani Patitis; Sri Wahyuni (Politeknik Kampar, 2024)
Public knowledge about health, the dangers of pesticides, environmentally friendly issues, make hydroponic vegetables are starting to be in deman. The increase in consumption of hydroponic vegetables provides a great opportunity for hydroponic vegetable businesses. The hydroponic system has many advantages compared to conventional systems,like environmentally friendly, hygienic and healthy products, faster plant growth, the quality of plant yields can be maintained and the quantity can be increased. The Community Service Team (PKM) has conducted a field survey and communication with the Salo Village regarding the problems they face. An agreement has been reached and a PKM program has been approved in the form of guidance and training on the hydroponic agricultural technology system on a household scale in Salo Village, Salo District, Kampar Regency, Riau. The extension material includes what is hydroponic cultivation, the importance of hydroponic cultivation for improving the family economy and various hydroponic media from simple materials. The team presents a 9-hole hydroponic system, hydroponics, seeds and plant nutrients. The vegetable seeds given are lettuce. The reason for choosing lettuce is because lettuce has high economic value, is more resistant to pests, has many types of variants, and is good for health. The condition of the residents of Salo Village has great potential for empowerment. The active participation of the residents of Salo Village to participate in counseling and hydroponic planting practices shows that the enthusiasm of the residents is very high. The activeness shown by participating in direct practice shows that there is additional knowledge and understanding of residents about hydroponics. This community service activity went succesfully and was achieved according to plan. Kata Kunci: Hidroponik, selada, penyuluhan